Improving the Ability to Understand the Concept of Rights and Obligations of Grade III Students Through the UTAHAWA Learning Media (Snakes and Ladders of Rights and Obligations) at SDN Jubellor Sugio - Ayu Safitri; Septia Fairis Ramadhani; Nurul Hidayatis Sadiya; Ribi Nava Aulia Mukti; Abdi Robbi Rahmatinda (Penerbit Presisi Pustaka, 2026)
Pancasila education plays a crucial role in shaping students' character, particularly in understanding rights and obligations in everyday life. However, conventional learning processes result in students being less active and experiencing difficulty understanding the material. This study aims to improve third-grade students' understanding of rights and obligations through the UTAHAWA (Snakes and Ladders of Rights and Obligations) learning media. The study used the Classroom Action Research (CAR) method, implemented in two cycles with planning, action, observation, and reflection. The study subjects consisted of 16 third-grade students at Jubellor Sugio Elementary School, Lamongan. Data collection techniques in this study included tests, observation, and documentation. The research findings indicate that the implementation of the UTAHAWA media has a positive impact on improving student learning outcomes. This is evident in the increase in students' average scores, from 48.6% in the pre-test to 66.6% in Cycle I, and again to 86% in Cycle II. Furthermore, students' learning completion rate also significantly increased to 94%. The use of educational games has been shown to create a more active, engaging, and enjoyable learning environment, making it easier for students to understand the concept of rights and obligations.